Observations on Factor VIII (Antihaemophilic A Factor) Stability in Rabbit and Rat Plasma Estimation of Factor VIII in Rat Blood by a New Method - Nilsson, D; Waaler, B. A (Thrombosis and Haemostasis, 1965)
1. Factor VIII activity of rat and rabbit plasma can be measured with a modification of the thromboplastin generation test.2. Using this method it can be shown that factor VIII activity is unstable on storage and on repeated freezings and thawings in oxalated plasma from the two animal species. The factor VIII activity is especially unstable in oxalated rat plasma, from which it disappears almost completely by four or more repeated freezings and thawings.3. A rat oxalated plasma, which had been frozen and thawed ten times, could be used as a factor VIII-free reagent in a simple one-stage test system for measurements of this factor in rat or rabbit plasma.4. The method developed may be used with rat tail capillary blood as test material, making repeated observations on rats possible. The use of the method is discussed.